Analisis Perbandingan Kapasitas Penyisipan Data dan Kualitas Citra Dalam Teknik Steganografi LSB dan MSB Menggunakan Peak to Signal to Noise Ratio dan Mean Squared Error - Ilham Fauzi; Mufida Khairani (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
This study discusses a comparison between the Least Significant Bit (LSB) and Most Significant Bit (MSB) methods in digital image steganography based on image quality parameters using the Mean Squared Error (MSE) value. The LSB method embeds secret information in the least significant bits of each pixel, while the MSB method embeds information in the most significant bits. The test results show that the LSB method produces very low MSE values, ranging from 0.1 to 2, thereby maintaining image quality with changes that are visually imperceptible. In contrast, the MSB method produces high MSE values, reaching 40 and above, indicating significant pixel intensity changes and a considerable decline in image quality. Based on these results, it can be concluded that the LSB method is more effective and secure for hiding data in digital images, as it preserves visual quality and is difficult to detect. Meanwhile, the MSB method is less recommended due to its susceptibility to detection and noticeable degradation of image quality.